The development of group influence on in-group identification: A multilevel approach. (March 2015) - Jans, Lise; Leach, Colin Wayne; Garcia, Randi L.; Postmes, Tom
Research on in-group identification typically focuses on differences in individuals' identification at the individual level of analysis. We take a multilevel approach, examining the emergence of group influence on identification in newly formed groups. In three studies, multilevel confirmatory factor analysis confirmed two dimensions of identification—self-definition and self-investment (Leach et al., 2008)—at both the individual and the group level. As expected, the group had greater influence on individuals' identification the more group members interacted with each other. This was shown in experiments with varying amounts of real interaction (Study 1), in a longitudinal study of student project groups (Study 2), and in a longitudinal study that experimentally mimicked the development of online communities (Study 3). Together, these studies support a developmental model of identification at the group level that has implications for the understanding of social identity and small-group dynamics.